Integrating Education for Sustainable Development in Biology: Effects on Systems Thinking and Sustainability Awareness - Francis Kung'u Mwangi; Alexandros Kaminas (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effect of integrating Education for Sustainable Development (ESD) in biology learning on students’ systems thinking skills and sustainability awareness, and to measure the magnitude of its impact compared to conventional teaching methods. Methodology: This study employed a quantitative quasi-experimental design with a pretest–posttest control group. The intervention used an Education for Sustainable Development (ESD)-based biology module, systems mapping tasks, and local environmental case studies. Instruments included a Systems Thinking Skills test and a Sustainability Awareness questionnaire. Data were analyzed using IBM SPSS (version 26) for Shapiro–Wilk, Levene’s test, independent samples t-test, and ANCOVA. Main Findings: The who received Education for Sustainable Development (ESD)-based biology instruction showed substantially higher gains in systems thinking skills and sustainability awareness compared to the control group. ANCOVA results confirmed a highly significant effect of the intervention (p < 0.001) with very large effect sizes (η² = 0.598 for systems thinking; η² = 0.525 for sustainability awareness). These findings demonstrate the strong impact of structured, contextual ESD integration in biology learning. Novelty/Originality of this study: The study provides new empirical evidence that a structured, context-based Education for Sustainable Development (ESD) approach in biology simultaneously and strongly enhances both systems thinking and sustainability awareness. Unlike prior studies focusing on single competencies or correlational data, this research applies a controlled quasi-experimental design, offering clearer causal evidence and a practical, replicable ESD model for secondary science education.